Respuesta :
Answer:
3^x + 12x -4
Step-by-step explanation:
f(x) = 3^x + 10x
g(x) = 2x - 4,
(f + g)(x) = 3^x + 10x + 2x - 4
Combine like terms
= 3^x + 12x -4
Answer:
(f + g)(x)= 3^x +12x -4
Step-by-step explanation:
To find (f+g)(x), we must add f(x) and g(x).
(f + g)(x)= f(x) + g(x)
We know that f(x)= 3^x + 10x and g(x)= 2x-4
Therefore, we can substitute these into the equation.
(f + g)(x)= (3^x+10x) + (2x-4)
Combine like terms. Add all the terms with an x.
(f + g)(x)= 3^x + (10x+2x) -4
(f + g)(x)= 3^x +12x -4
(f + g)(x) is 3^x +12x -4